Riverine Eco-Tourism and Sustainable Development in Assam, India: Transforming the Brahmaputra Corridor - Mahanta, Barnali (Eco-Tourism and Sustainable Development, 2026)
Riverside eco-tourism is increasingly positioned as a pathway for sustainable urban development in cities located along major river systems. Despite this growing interest, tourism planning on riverbanks often overlooks the complex interactions between cultural traditions, ecological processes, governance structures, and climate change. The results reveal that tourism models are largely influenced by religious and cultural activities, particularly pilgrimage-oriented travel, while recreational, leisure, and experience-based tourism opportunities remain underdeveloped. Environmental challenges such as seasonal floods, riverbank erosion, and water level fluctuations, as well as inadequate tourism infrastructure and fragmented institutional arrangements, significantly limit both tourism’s performance and long-term resilience. The local community’s perspective reflects a dual narrative: while tourism is seen as a source of livelihood and economic prospects, concerns persist about environmental degradation, unequal distribution of benefits, and limited community participation in decision-making. Based on these empirical insights, the study proposes a corridor-based riverside eco-tourism framework that places tourism within a broader cultural-ecological system rather than treating it as an isolated sector. The framework emphasizes the integration of cultural activity nodes, environmental buffer zones, river-based mobility networks, and holistic governance systems, while clearly recognizing the institutional and financial constraints that exist. Instead of encouraging the development of tourism separately, the proposed approach prioritizes adaptive, climate-responsive, and socially equitable planning at the river corridor scale. Based on conceptual developments in empirical evidence, the study offers river tourism scholarships and provides policy-relevant guidance for sustainable tourism planning in large, climate-sensitive river systems.